Troponin I measurement after acute myocardial infarction and its correlation with left ventricular ejection fraction - Shah, Mohita; Kothari, Prafful (International Journal of Advances in Medicine, 2022)
Background: After acute myocardial infarction (MI), a patient’s prognosis is closely related to the extent of irreversibly damaged myocardium. The evaluation of infarct size after acute MI (AMD) is important for predicting the subsequent clinical course. Cardiac troponin I (cTnl) is accepted as a highly reliable biochemical marker for detecting myocardial damage, and its use in the diagnosis of acute MI (AMI) is increasing. Its concentration is unaffected by thrombolysis after the first12 hours, following which it shows a stable plateau for about 48 hours. Methods: This study investigated the value of a single cTnl concentration, estimated 12-48 hours after admission, to provide an integrated measurement of the degree of cardiac damage following first acute MI, and its correlation with left ventricular ejection fraction (LVEF). This study of troponin I measurement after acute MI and its correlation with LVEF was conducted during the period between October 2019 and October 2021 at SMIMER hospital, Surat. Results: This study shows a strong negative correlation between cTnI concentration measured between 12-48 hours post MI and echocardiographic LVEF. It was also found that cTnl concentration more than 3.8 ng/ml is a sensitive (100%) and specific (78.12%) indicator of LVEF <40% after a first acute MI. It can be considered as a significant prognostic marker. Conclusions: In conclusion, cTnl shows excellent promise as a marker of infarct size, and for the assessment of LVEF; and may potentially replace the CPK-MB as the cardiac specific marker for AMI detection.